PREVALENCE OF TONGUE HEMANGIOMAS IN WESTERN RAJASTHAN, A CROSS- SECTIONAL STUDY (Journal of Pharmaceutical Negative Results, 2022)
Hemangioma is a developmental vascular malformation capillaries that do not involute but persist and grow very slowly over years. They are mostly found on the cheeks, upper lip, and eyelids, and rarely in the oral cavity, especially on the tongue. The diagnosis of hemangioma is mainly based on history, clinical evaluation and diascopy test Here in this study, prevalence of hemangioma was observed to be 1.2% with a male female ratio 5:1. Further studies should be conducted to determine correlation with age sex and site of occurrence of hemangioma.